2022
DOI: 10.3390/ijerph191912751
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Paternal Mental Health and Informal Support Networks: Reflections on the Impact of the COVID-19 Pandemic

Abstract: Paternal mental health remains an under-researched area in the UK. Consequently, father-focused formal and informal support provisions fail to address the complex emotional and psychological wellbeing needs of fathers. Drawing on data from twenty semi-structured interviews with fathers in the York area, this study seeks to better understand how access to and participation in informal support networks is influenced by gendered perceptions and the impact hegemonic perceptions of masculinity have on fathers’ acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Fathers that were on the furlough scheme had much more time with their family compared to fathers that still had to work from home. While the pandemic presented different challenges, such as the inability to access informal support [ 63 ], fathers felt that they did not have to navigate the challenge of negotiating the transition to work. Working from home offered a reason for fathers to be at home and not have to feel guilty or navigate gender and masculine perceptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fathers that were on the furlough scheme had much more time with their family compared to fathers that still had to work from home. While the pandemic presented different challenges, such as the inability to access informal support [ 63 ], fathers felt that they did not have to navigate the challenge of negotiating the transition to work. Working from home offered a reason for fathers to be at home and not have to feel guilty or navigate gender and masculine perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 lockdown created an opportunity for fathers to be physically present at home, which resulted in more engagement in family activities [ 62 ]. There was a positive increase in shared parenting responsibilities, although lack of access to informal support proved challenging and impacted on fathers’ mental health [ 63 ]. While it has been demonstrated that the COVID-19 lockdown had a negative impact on paternal experience and father–baby bonding as a result of fathers being excluded from maternity care, it is essential to explore fathers’ experiences of leave entitlement post-birth [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that the proportion of females would be higher than that of males. However, evidence from the UK suggests that fathers expressed masculinity traits that prevent them from seeking help for their mental health problems during COVID-19 [30]. The COVID-19 lockdown could be a barrier for them to find informal support for their mental health as they thought that other non-parent people with different experiences would not understand the hardship during this crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of information leaves fathers internalizing the notions of stoicism and emotional detachment, making them less likely to seek support for their challenges or mental health [56]. Cultural perceptions that perinatal mental health services are predominantly focused on maternal mental health [44], coupled with the absence of inclusive healthcare practices [38], instil in fathers the belief that they need to demonstrate strength, suppress emotions, and concentrate on supporting the mother.…”
Section: "I Think They Spend More Time Talking About the Whole Birth ...mentioning
confidence: 99%
“…Nevertheless, men tend to internalise hegemonic masculine ideals and are predisposed to suppressing their mental health challenges, as opposed to actively seeking support [36]. Consequently, individuals who internalise notions of stoicism and emotional detachment are more inclined to eschew addressing their mental health issues due to apprehensions about negative perceptions from friends and family [56].…”
Section: Introductionmentioning
confidence: 99%